About energy ekspertizеs of electrical networks of energy systems - V. Radionova, Olga; R. Sitdikov, Rashid (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: one of the most important factors in the sustainability of the system of social, economic and environmental parameters that determine the quality of life of the population, and an indicator of the effectiveness of public administration, is an efficient electric power industry. With the development and complexity of electric power systems (EPS) - diversification of generation sources, digitalization, intellectualization, rapid development of renewable energy sources (RES), the emergence of microgrids, etc., there is a need to periodically conduct and improve the efficiency of energy expertise of EPS facilities, especially electrical networks. Aim: justification of the frequency and expansion of the tasks of conducting energy examinations for comparative assessments of the operational properties of electrical network equipment: safety, environmental friendliness, reliability, survivability, mode optimization, power quality, etc., which will ensure the trouble-free and efficient operation of the EPS, as well as its further development in Uzbekistan. Methods: a systematic analysis of the results of energy examinations of electrical networks is used, as well as the study of foreign experience in conducting examinations of power installations and a comparative analysis of various types of energy examination. Results: the corresponding range of tasks is justified and proposed, expanding the complexity and efficiency of periodic energy examinations of electrical networks; appropriate approaches for their practical implementation are proposed.